An Investigation of Cyber Crimes from the Point of View in Imamieh (Iran) Jurisprudence - Vahedi Kabiri, Fatemeh (2020)
The aim of this study was an investigation of cybercrime from the point of view of Imamieh (Iran) jurisprudence. The present study is a descriptive-analytical investigation. The importance of the topic has forced the author not only to review the ideas of academics, but also to provide a foundation of recognition for cybercrime. The results show that jurists believe that acts of depravity should be prosecuted through punishment; and in some cases they have condemned it as mofsed-e-filarz, which is punishable by death. Likewise, the points of view of jurists have been investigated; research has been based on research. Through the investigations carried out, it is made clear that certain crimes that have been used by social networks to decrease chastity in society include the disclosure of adultery, pimping, pornography, etc., which have been referred to by legislators and saints imams and the Prophet. . In the first step, these crimes are not only against the offender, but also target and weaken the foundations of the most important units of any society, which are families.